1999
DOI: 10.1080/13623699908409479
|View full text |Cite
|
Sign up to set email alerts
|

III: Mental health initiatives as peace initiatives in Sri Lankan schoolchildren affected by armed conflict

Abstract: The Health Reach Sri Lanka project (1993-96) is described. It was a school-based assessment of children's exposure to war-related events and the presence of psychological distress, undertaken in six communities in parts of Sri Lanka variously affected by armed conflict. Its objectives, methods and results are presented. The research project aimed to raise national awareness of the psychosocial effects of armed conflict on children, using a community-development approach to local capacity building, based on the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0

Year Published

2002
2002
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(21 citation statements)
references
References 4 publications
1
20
0
Order By: Relevance
“…Similar dose gradients have been observed in research on child maltreatment (Masten and Wright, 1998). Clearly, 50-80% of children will show at least some signs of PTSD when they directly experience intense threats, as posed, for example, by tear-gas attacks (Thabet and Vostanis, 2000), witnessing the murder or beating of their parents (Chase et al, 1999;Sack et al, 1999;Thabet and Vostanis, 1999), or by neardeath experiences (Sack et al, 1999). Many studies of trauma in children have found that direct injury to self, parents, and other close people is associated with more trauma symptoms .…”
Section: Personal Exposure To War and Terrorismsupporting
confidence: 53%
See 1 more Smart Citation
“…Similar dose gradients have been observed in research on child maltreatment (Masten and Wright, 1998). Clearly, 50-80% of children will show at least some signs of PTSD when they directly experience intense threats, as posed, for example, by tear-gas attacks (Thabet and Vostanis, 2000), witnessing the murder or beating of their parents (Chase et al, 1999;Sack et al, 1999;Thabet and Vostanis, 1999), or by neardeath experiences (Sack et al, 1999). Many studies of trauma in children have found that direct injury to self, parents, and other close people is associated with more trauma symptoms .…”
Section: Personal Exposure To War and Terrorismsupporting
confidence: 53%
“…Examples include the Holocaust (Sagi-Schwartz et al, 2003), the Belfast riots in Northern Ireland (Lyons, 1979), the Iraqi occupation of Kuwait (Hadi and Llabre, 1998), the ongoing saga of ethnic rivalry in Sri Lanka (Chase et al, 1999), the effects of the current situation in the Middle East (Schwarzwald et al, 1993;Thabet and Vostanis, 1999;Thabet et al, 2004), and ethnic cleansing in Cambodia (Mollica et al, 1997) or Rwanda (Dyregrov et al, 2000).…”
Section: Personal Exposure To War and Terrorismmentioning
confidence: 99%
“…However, over the last 35 years Sri Lanka has witnessed many natural and man-made disasters including two armed conflicts in the south, a civil conflict in the north and the tsunami disaster in 2004 [23,24]. The adverse impact of these exposures on child mental health has received some limited investigation, but impacts on education have not been considered [8,10,25-27]. Utilizing data from a large survey of school children in Sri Lanka, we sought to investigate the associations of absenteeism with previous conflict and tsunami exposure and to investigate the role of mental disorder in these associations.…”
Section: Introductionmentioning
confidence: 99%
“…In Sri Lanka, community reconstruction in conflict areas has addressed disability access problems, but has also occasionally required relocation of valued public services such as transportation and recreation facilities. Such relocation has to be done with particular sensitivity or there is a risk of increasing tensions within communities that are still suspicious of each other [43]. …”
Section: Discussionmentioning
confidence: 99%